Capital Humano e Desenvolvimento Econômico no Rio Grande do Sul: Uma Abordagem Multivariada - Nilson Luiz Costa (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2017)
This article proposes an analysis from the theories linking human capital to economic development process. The method used consists of multivariate statistical techniques, particularly the Exploratory Factor Analysis and Conglomerates Analysis. Statistics were selected from 496 municipalities in the state of Rio Grande do Sul/Brazil according to their capacity to represents the dynamics of income concentration, quality of education and health, poverty, education and formal work. Among the results, there is a positive and direct association between levels of formal education and economic development, which validates the theoretical contributions of Theodore William Schultz and other authors that stem from their lineage. The results point to the importance of breaking the current paradigms and think education policy beyond the rhetoric of official speeches and overcome the current challenges.